Peran Work Engagement Pada Pengaruh Beban Kerja Terhadap Kepuasan Kerja Di CV. Devano Silver Gianyar - I Kadek Ova Rionaldi; Ketut Elly Sutrisni (Jurnal Ilmiah Manajemen, Ekonomi dan Akuntansi, 2026)
The level of employee job satisfaction in Indonesia has attracted the attention of various survey institutions. Therefore, comparing survey results is important to provide a more comprehensive picture of employee job satisfaction in Indonesia. This study aims to determine the role of work engagement in the influence of workload on job satisfaction at CV. Devano Silver Gianyar. The sampling technique used in this study was saturated sampling, with a sample size of 45 employees. Data were collected using questionnaires and documentation, and the analysis technique used was a variance-based structural equation model or component-based structural equation model, also known as Partial Least Squares (PLS). Based on the analysis, this study shows that workload has a negative and significant effect on job satisfaction. These results indicate that increasing workload has a negative and significant impact on job satisfaction among employees at CV. Devano Silver Gianyar. Workload has a negative and significant impact on work engagement. These results indicate that increasing workload has a negative and significant impact on work engagement among employees at CV. Devano Silver Gianyar. Work engagement has a positive and significant impact on job satisfaction. These results indicate that increasing work engagement has an impact on job satisfaction among employees at CV. Devano Silver Gianyar. Work engagement can act as a mediating variable in the influence of workload on job satisfaction. The results indicate that higher work engagement stemming from effective workload management will increase job satisfaction among employees at CV. Devano Silver Gianyar.